Lipid analysis of tear fluid as a diagnostic tool for meibomian gland dysfunction - L.R. Takhauova; A.A. Guseva; A.A. Krylova; O.I. Krivosheina (РМЖ "Клиническая офтальмология")
L.R. Takhauova1,2, A.A. Guseva1, A.A. Krylova1, O.I. Krivosheina1 1Siberian State Medical University, Tomsk, Russian Federation 2Seversk Biophysical Scientific Center of the Federal Medical Biological Agency of Russia,   Seversk, Russian Federation The tear film lipid layer plays a crucial role in maintaining ocular surface homeostasis by preventing excessive evaporation of the aqueous layer and reducing heat transfer from the corneal and conjunctival surface. The lipid composition of the tear film is unique and consists of two main layers: the outer (nonpolar lipids) and the inner (polar lipids). The thick outer layer of the tear film is composed of non-polar lipids that lack internal distributed charge, while the thin inner layer is formed by polar lipids with positive and negative charges at the ends of the molecule. Both types of lipids are synthesized in the meibomian glands (MG) and contribute to tear film stability. Meibomian gland dysfunction (MGD) alters the composition and physical properties of lipids, leading to pathological changes in both the MG and tear film. In meibomian gland dysfunction (MGD), the meibum thickens and acquires a higher melting point than normal. This leads to a decrease in the amount of nonpolar and amphiphilic lipids in the meibomian gland secretion and tear film. Consequently, the protective effect of the tear lipid layer is impaired, and its stability is compromised. Lipid mapping analyzes the lipid composition of biological samples, such as tear fluid, to study the mechanisms of the development and progression of various ocular surface diseases, including dry eye syndrome, MGD, and recurrent blepharoconjunctivitis. This method provides fundamental data on the properties of the tear film in various ocular surface diseases. It has the potential to establish hallmarks of disease course and develop personalized treatment approaches for specific clinical cases. Keywords: tear, tear film lipids, ocular surface, meibomian gland dysfunction, lipid analysis. For citation: Takhauova L.R., Guseva A.A., Krylova A.A., Krivosheina O.I. Lipid analysis of tear fluid as a diagnostic tool for meibomian gland dysfunction. Russian Journal of Clinical Ophthalmology. 2024;24(2):83–87 (in Russ.). DOI: 10.32364/2311-7729-2024-24-2-7.